Mollison's blood transfusion in clinical medicine - Klein, Harvey G. (Wiley Blackwell, John wiley & Sons Ltd, 2014)
"Mollison's Blood Transfusion in Clinical Medicine is an icon in the field of transfusion and the first edition was published in 1951. The book arose from the concept of the transfusionist, as both scientist and expert consultant. For many years, this text has provided the primary, and often the sole, reference for detailed information and practical experience in blood transfusion. The book is completely revised and updated throughout to include the latest advances and developments in the field"--Provided by publisher.